Pengukuran Sikap Keagamaan melalui Skala Sikap dalam Pendidikan Agama Islam - Mahfud Heru Fatoni; Baron Santoso; Hamid Syarifuddin; Achmad Rasyid Ridha (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to identify and assess the types of attitude scales utilized in Islamic religious education, offering recommendations for their application in this field. The article is based on a library research method, where the concepts and definitions found were sorted and selected for data collection. The analysis was carried out using two main approaches: deductive and inductive. The study identified several attitude scales, including the Likert scale, Guttman scale, semantic differential, and rating scale. The application of these measurement scales such as the Likert scale, Guttman scale, semantic differential, and rating scale provides effective tools for assessing students' attitudes, perceptions, and comprehension of religious teachings. The implication of this research is to lay the groundwork for developing more efficient and precise instruments for evaluating students' religious attitudes, which will ultimately enhance the quality of Islamic Religious Education across various educational levels.